Politik Islam: Analisis Pemikiran Ibn B?jjah Dalam Kit?b Tadb?r Al-Mutawahhid - Abdul Kohar (Politea : Jurnal Politik Islam, 2020)
Ibn B?jjah was the first Muslim philosopher in Spanish. His full name is Ab? Bakr Muhammad ibn yahya al-Sh?'igh al-Tuj?b? al-Saraqust?. Ibn B?jjah is also known by the laitin name Avempace, he is a rationalist philosopher. Many of his ideas about political, especially in the book of Tadb?r al-Mutawa??id. Ibn B?jjah said that a government have to be mutawa??id, and mutawa??id should be able to control themselves and be able to control lust, not to be dragged into the mainstream of society. The purpose of this research first the writer wants to say that the government (leader) is a transformation for his society, then democratic systems isn’t just saying "from the society to the society", but democracy have to be motivated by the society who have common sense, wich isn’t appear on personal interests, more precisely good society will produce good leaders. This type in this research is a library research by presenting qualitative-interpretative data, where the main object is the available library books, certainly the books are related to the subject of this research. This research uses two data sources, namely primary and secondary data. The primary data in this research were obtained books written by Ibn B?jjah's books (kit?b) such as the Book of Tadb?r al-Mutawa??id and Ris?lah al-Ittish?l. While the secondary data is journal, the articles are also book’s that discuss Ibn B?jjah in particular. The result of this paper is that the essence of the State's purpose is identical with the purpose of human life. Nations and peoples are united in their pursuit of happiness.